(untitled) (Community Based Medical Journal, 2013)
The post partum diastasis ( means separation) of pubic symphysis is an uncommon disease. It causes acute pelvic pain. Manual pressure to the pelvis in a latero-lateral and antero-posterior direction worsens the condition. The diagnostic test for this condition is an anteroposterior X-ray of the pelvis. Here we present a case following spontaneous vaginal delivery. The conservative treatment is able to obtain good results. If this disease is underestimated the patient can develop chronic pain. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14190 Community Based Medical Journal Vol.2(1) 2013 73-75